Resazurin MicrotiterAssay (REMA) modificado para detecção de resistência à ciprofloxacino e linezolida em micobactérias de crescimento rápido - Castilho, Aline Lemes (2013)
The rapidly growing mycobacteria (RGM) comprise a group of non-tuberculous mycobacteria (NTM) and contains species of pathogenic microorganisms which cause various types of localized and disseminated infections, especially in skin, bones and joints. These infections are in most cases associated with immunocompromised patients and require long term treatment. The susceptibility test recommended by the Clinical and Laboratory Standards Institute (CLSI) for RGM pathogenic requires visual reading which makes it very subjective. The method resazurin microtiter assay method (REMA) has been used in research to determine the minimum inhibitory concentration (MIC) for antituberculous drugs because it is simple, low cost and provide faster results compared to traditional methods. The aim of this study was to evaluate the in vitro effect of REMA modification for MIC determination to MCR to ciprofloxacin and linezolid in the cultivation of bacillus in culture medium containing resazurin. Were used for the study Mycobacterium chelonae, M. abscesus, M. smegmatisand M. fortuitum, and the results were compared to the susceptibility test recommended by CLSI and REMA. There was no difference in MIC for linezolid and ciprofloxacin when adding resazurin directly in the culture medium for the isolates studied. The modification of REMA by using culture medium containing resazurin previously shown to be efficient, reproducible, fast, inexpensive, easy to perform and interpret the detection of resistance to linezolid and ciprofloxacin in MCR.